Customer Satisfaction in Using Shopee Marketplace: Gender based Comparison - Prataga, Dimas Ikbal; Santoso, Ignatius Hari (Review of Management and Entrepreneurship, 2022)
This study analyzes the information quality, perceived price, and system quality predictors of Shopee customer satisfaction. Also, in this research, we test gender as a moderator construct. This study used 100 samples. Using Smart PLS version 3, we can find that three latent constructs are significant predictors of Shopee customer satisfaction. However, gender as a moderator cannot have a significant effect. For further research, we suggest the additional construct, such as online review to be tested as a predictor. Keywords: information quality, perceived price, system quality